Navigating the ERP Landscape: Unveiling the Key Drivers in Enterprise Resource Planning Success - A Comprehensive Literature Exploration - Teguh Raharjo; Venera Genia; Aji Prasetyo; Rahmita, Fehmi (The Indonesian Journal of Computer Science, 2023)
Organizations require information systems as a means of aiding decision-making processes. Enterprise Resource Planning (ERP) systems serve as information system tools that enhance work efficiency. They are considered the optimal solution for organizations seeking a competitive edge. The successful implementation of ERP systems offers numerous benefits to organizations. It is essential to note that while some organizations have encountered difficulties using ERP systems, others have succeeded. Implementing ERP systems poses a challenge for organizations, and this study aims to identify the critical success factors with ERP systems and get to know what category is most important to implementing ERP in an organization. This research identifies and categorizes the top five CSFs for successful ERP implementation: training and job redesign, adequate ERP software selection, clear goals and objectives, business process reengineering, and implementation strategy and timeframe. These CSFs are vital for organizations of all scales, offering a holistic framework for effective ERP integration. Through systematic analysis, the study maps these CSFs into four dimensions: Project Strategy, Project Structure, Information Systems, and People Management, highlighting the interplay between technology and human factors. This research underscores the enduring significance of ERP systems in the globalized business landscape and calls for continued exploration of evolving CSF trends to ensure ongoing organizational competitiveness and success. By following the outlined procedures, this study can be applied by organizations of different scales, including small and large businesses, to achieve effective ERP implementation. Integrating ERP systems will demonstrate advantages for organizations over the short and long run within the market context.